Study on groundwater quality in and around solid waste landfill site at Tiruchirappalli, Tamil Nadu, India - Venkatesan, G; Swaminathan, G; Nagarajan, Ramasamy (Inderscience Enterprises Ltd., 2013)
The groundwater chemical quality changes adjacent to solid waste disposal area of Tiruchirappalli metropolitan area was evaluated by groundwater samples collected from three bore wells in the vicinity (December 2006 to November 2007) for one year. The present study area is the place where the Tiruchirappalli solid wastes are land filled. Continuous dumping of solid wastes has rapidly changed the land use pattern, which affects the groundwater quality of the adjacent region. This study has investigated the chemical characteristics and the contamination of groundwater in relation to land use. Most of the water samples were not conforming to the standards for the drinking water quality. The groundwater near the landfill site of Tiruchirappalli City was found to be not suitable either for domestic or irrigation purposes. The groundwater of the study area was found to be affected by temporary as well as permanent hardness. The results of factor analysis indicates that the levels of Ca2+, Mg2+, Cl− and SO4 2− ions maybe due to pollution from solid waste sources and natural weathering reactions. This paper clearly shows the effect of landfill on groundwater quality and emphasises the necessary precautionary steps to control during the extension of landfill site in the adjacent areas.